Population balance modeling for crystallization processes - Kuah, Kenny Wen Cheong. (2010)
Crystallization is a separation process involving mechanisms such as nucleation, growth, aggregation and breakage. Population Balance Model (PBM) is widely used to describe the behavior of crystallization processes. PBM can be used to determine the crystal size distribution in the crystallization process to optimize the product specifications. PBM involves hyperbolic partial differential equations (PDE) which often do not have analytical solution. Therefore, various numerical methods are employed to solve the model equations, called population balance equations (PBE). In this report, hierarchical two-tier method algorithm is evaluated. This technique is based on employing individual rates of nucleation, growth and coagulation to update the population size distribution (PSD). The first step is the calculation of the rates of nucleations, growth and coagulation by solving a set of equations. Subsequently, this information is used to update the PSD. IN solving the coagulation kernel, a semi-analytical solution strategy is adapted which reduces the computational requirements yet ensuring the consistency of properties such as number and mass particles. A computationally efficient solution technique would be useful in presenting PBM and this serves as the motivation for the suitability of two-tier method algorithm and its application.